2002
DOI: 10.1046/j.1523-1755.2002.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Middle molecule and small protein removal in children on peritoneal dialysis

Abstract: Solutes removed during PD tend to decrease following an increase in molecular weight of the substance. Since anuric patients are at higher risk of middle molecule and small protein accumulation, more attention should be paid to the removal of middle molecules. Further studies should be undertaken to evaluate whether removing them has a clinical impact and to determine their threshold levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 18 publications
2
26
1
1
Order By: Relevance
“…The peritoneal clearance of molecules decreases with increasing molecular size [11,12], whereas the contribution of renal clearance increases accordingly. However, a recent cross-over study comparing high-flow CCPD and standard CAPD did not observe any significant differences in peritoneal substrate clearances for molecules up to a mass of beta 2 -microglobuline (11.8 kDa, [13]).…”
Section: Introductionmentioning
confidence: 98%
“…The peritoneal clearance of molecules decreases with increasing molecular size [11,12], whereas the contribution of renal clearance increases accordingly. However, a recent cross-over study comparing high-flow CCPD and standard CAPD did not observe any significant differences in peritoneal substrate clearances for molecules up to a mass of beta 2 -microglobuline (11.8 kDa, [13]).…”
Section: Introductionmentioning
confidence: 98%
“…These results can be explained by the relationship between the renal and peritoneal Kt/V urea and the weekly renal and peritoneal C cr , where decreasing renal elimination is associated with increased peritoneal clearance. Montini et al [14] demonstrated that in children with residual diuresis, CysC is removed mainly by renal creatinine clearance (62.8%) and that plasma CysC is significantly correlated with renal inulin clearance. These researchers also showed that solutes removed during PD tended to decrease with an increase in molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, it is freely filtered through the glomeruli and then catabolized in the proximal tubules; consequently, it is not normally secreted [13]. The intermediate size of CysC makes it dialyzable and a "middle molecule" marker of toxin removal [14]. Previous studies have suggested that serum CysC might be a superior marker for the GFR than creatinine, because it is independent of age and other factors, such as height and muscle mass [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Middle-sized molecules and phosphate removal is slow and equilibration with plasma levels only occurs with a long dwell [207]. Removal of middle-sized molecules and low-molecular-weight proteins, such as b 2 -microglobulin and leptin, mainly depends on residual renal function [183,21]. Moreover, an increasing restriction coefficient was reported for macromolecules with time on chronic PD, which is associated with increased size selectivity and a reduced peritoneal permeability for higher-molecular-weight solutes [32].…”
Section: Clearance Of Middle-sized Molecules and Phosphatementioning
confidence: 99%